2014
DOI: 10.5041/rmmj.10150
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Margins in Transoral Laser and Robotic Surgery

Abstract: The growing practice of endoscopic surgery has changed the therapeutic management of selected head and neck cancers. Although a negative surgical margin in resection of neoplasm is the most important surgical principle in oncologic surgery, controversies exist regarding assessment and interpretation of the status of margin resection. The aim of this review was to summarize the literature considering the assessment and feasibility of negative margins in transoral laser microsurgery (TLM) and transoral robotic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 54 publications
5
25
0
Order By: Relevance
“…The importance of negative surgical margins to prevent the patient from repeat surgery or further oncologic therapy is well understood. Previous case series examining TORS in various head and cancers report a positive margin rate between 0% to 33% . In our study, 16.5% of TORS patients had positive margins.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The importance of negative surgical margins to prevent the patient from repeat surgery or further oncologic therapy is well understood. Previous case series examining TORS in various head and cancers report a positive margin rate between 0% to 33% . In our study, 16.5% of TORS patients had positive margins.…”
Section: Discussionsupporting
confidence: 50%
“…In our study, 16.5% of TORS patients had positive margins. It is hypothesized that TORS, and possibly endoscopic or microscopic surgery, offers better visualization and accessibility than standard open surgery—and as a result allows the surgeon to perform more complex operations …”
Section: Discussionmentioning
confidence: 99%
“…There is debate regarding the benefits of TORS versus nonrobotic endoscopic surgical approaches for oropharyngeal SCC. Several authors have suggested that TORS provides better visualization and exposure for oropharyngeal SCC compared to TLM and other nonrobotic transoral approaches . Although both TORS and TLM are limited by a lack of haptic feedback, advocates of TORS cite the ability to maneuver with 2 hands and to overcome line‐of‐site limitations as possible advantages of TORS over TLM .…”
Section: Discussionmentioning
confidence: 99%
“…While en bloc resection still remains a key surgical principle, the extension of surgical oncology into more complex anatomical areas and technological advances (ie, endoscopic mucosal resections, transoral laser microsurgery) highlight the need to reconsider the potential merits of piecemeal tumor removal. 1,2 Piecemeal resections are controversial because they result in fragmentation of the removed specimen, compromising its integrity and complicating confident histopathologic evaluation for the adequacy of excision. While in certain areas of the body, such as the skull base or larynx, piecemeal tumor removal may be justified by anatomical constraints 3 or functional imperatives 4 (ie, preservation of voice and deglutition), the apparently increasing use of the piecemeal approach in anatomically simpler and more accessible parts of the human body is more difficult to understand.…”
mentioning
confidence: 99%